1999
DOI: 10.1021/jp9927451
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Potential-Dependent Transformations in Sulfur Adlayers on Au(111) Electrodes

Abstract: The potential (E)-dependent transformations of adsorbed sulfur on Au(111) in 0.1 M NaOH + 3 × 10-3 M Na2S have been followed by in situ STM imaging. When E is changed from −0.6 to −0.8 V, the transformation from rectangular S8 surface structures to a √3 × √3 R30° S lattice takes place. This process involves sulfur atom desorption, the formation of rectangular tetramerical surface structures, and the displacement of sulfur atoms to nearest hollow sites. When E moves from −0.8 to −1.0 V fast desorption of the √3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
133
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(154 citation statements)
references
References 20 publications
(37 reference statements)
20
133
1
Order By: Relevance
“…5c is 47 • . The brightness difference between the two S atoms can be due to the different adsorption sites, which has been reported previously [18][19][20][21]. The bright spot in STM image corresponds to the S atom in fcc position and the dark one in hcp position.…”
Section: Adlayer Structure Of Htlsupporting
confidence: 74%
“…5c is 47 • . The brightness difference between the two S atoms can be due to the different adsorption sites, which has been reported previously [18][19][20][21]. The bright spot in STM image corresponds to the S atom in fcc position and the dark one in hcp position.…”
Section: Adlayer Structure Of Htlsupporting
confidence: 74%
“…15 This so-called electrocompression was also found for the I adlayers on Au͑111͒ [16][17][18][19] and Ag͑111͒. 20 It was also reported that the adlayer structures of S on Au͑111͒ 21, 22 and Ag͑111͒ 23 were dependent on the electrode potential in solution. On Au͑111͒, a () ϫ ))R30°s tructure of S adlayer was observed at negative potentials by in situ STM, 21,22,24 whereas at positive potentials, S clusters like S 8 rings were found with an increase in coverage.…”
mentioning
confidence: 63%
“…When the electrode potential was scanned in the positive direction, triangle clusters made of three S atoms were arranged so as to form a wellordered (ͱ7 ϫ ͱ7)R19.1°structure on Ag͑111͒. 23 As described above, S atoms on Au͑111͒ 21, 22 and Ag͑111͒ 23 in aqueous solutions presented various structures depending on the electrode potential. However, to our knowledge, there has been no in situ STM study performed in solution for the adlayer structure of S on Cu͑111͒.…”
mentioning
confidence: 99%
“…The presence of different in plane orientations could be connected with a possible reconstruction of first S overlayer different from the ( √ 7 × √ 7)R19.1 • structure. On the similar S-Au(1 1 1) system, the S layer presents different coexisting phases (( √ 3 × √ 3)R30 • , trimers and ottomers) which evolve dynamically from one phase to another with time at constant potential [43]. The dynamics strongly depends on the applied potentials.…”
Section: Analysis Of Cds Layers Deposited By Ecalementioning
confidence: 99%